2014
DOI: 10.1155/2014/275735
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fluid-Structure Interaction in the Effects of Pin-Through-Hole Diameter during Wave Soldering

Abstract: An effective simulation approach is introduced in this paper to study the thermal fluid-structure interaction (thermal FSI) on the effect of pin-through-hole (PTH) diameter on the wave soldering zone. A 3D single PTH connector and a printed circuit board model were constructed to investigate the capillary flow behavior when passing through molten solder (63SnPb37). In the analysis, the fluid solver FLUENT was used to solve and track the molten solder advancement using the volume of fluid technique. The structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…To the best of the authors' knowledge, no study has reported on the influence of PCB configurations during the wave soldering process by using the coupling technique. Therefore, the present study extends the authors' work (Abdul Aziz et al, 2014a) and aims to investigate the influence of different PCB (sound card) configurations on temperature distribution, heat transfer coefficient, thermally induced displacement and stress. The understandings of these aspects are important to the designer prior to designing the sound card.…”
Section: Introductionmentioning
confidence: 78%
“…To the best of the authors' knowledge, no study has reported on the influence of PCB configurations during the wave soldering process by using the coupling technique. Therefore, the present study extends the authors' work (Abdul Aziz et al, 2014a) and aims to investigate the influence of different PCB (sound card) configurations on temperature distribution, heat transfer coefficient, thermally induced displacement and stress. The understandings of these aspects are important to the designer prior to designing the sound card.…”
Section: Introductionmentioning
confidence: 78%
“…The ability of this simulation technique to handle FSI problems had been proven in the author's recent studies [14,15,17]. The simulation predictions were validated by the experimental measurements.…”
Section: Numerical Study -Thermal Fsi Analysismentioning
confidence: 94%
“…4 illustrates the comparison of the experimental and simulation solder profile. Moreover, the simulation results had been validated in term of temperature [30], filling profile [14,15] and filling level [17]. Thus, this simulation technique is expected to provide the best visualization for the present study.…”
Section: Numerical Study -Thermal Fsi Analysismentioning
confidence: 99%
See 2 more Smart Citations